The Influence of Tourist Visits on the Entrepneursip Motivation Around Salopi Beach Pinrang District - Nurfadila, Nurfadila; Niswaty, Risma; Nur, Andi Cudai (Jurnal Administrasi Bisnis, 2025)
Nurfadila, 2023. The influence of tourist visits on entrepreneurial motivation around Salopi Beach, Pinrang Regency. Thesis. Business Administration Study Program. Faculty of Social Sciences and Law. Makassar State University. Guided by Risma Niswaty and Andi Cudai Nur. This study aims to determine how the influence of tourist visits on entrepreneurial motivation around Salopi Beach, Pinrang Regency. To achieve this goal, researchers use indicators to measure these variables. In the variable of tourist visits, the indicators used are tourist income, travel costs to tourist attractions, tourist leisure time, and tourist attraction facilities. As for the variable of entrepreneurial motivation, the indicators used are the need for achievement, the need for power, and the need for affiliation. In this study, the research method used is a type of quantitative research, with data collection techniques carried out through observation, questionnaires and documentation. The sample used in this study was 30 respondents. Data was obtained from the results of research processed using data analysis and using the help of SPSS software program version 26 consisting of validity tests, reality tests, normality tests, simple linear regrrsi analysis, product moment correlation and coefficient of determination. The results showed that the indicators used on each of these variables showed that tourist visits were in the very good category. For indicators on the variable of entrepreneurial motivation is in the very good category. Based on the coefficient of determination test, the value of R2 is at high intervals, which means that tourist visits have a high influence on entrepreneurial motivation around Salopi beach, Pinrang Regency.                                                            Keywords: tourist visits, entrepreneurial motivation, Salopi Beach.